Reversing Hydrogel Adhesion Property via Firmly Anchoring Thin Adhesive Coatings. (26th December 2021) - Feng, Haiyan; Ma, Yanfei; Zhang, Zhizhi; Yang, Song; Ma, Zhengfeng; Zhang, Yunlei; Ma, Shuanhong; Yu, Bo; Cai, Meirong; Pei, Xiaowei; Zhou, Feng
Abstract: Hydrogels, exhibiting wide application prospects in soft robotics, tissue engineering, implantable electronics, etc., upon functioning often require to adhere to substrates especially in wet environments despite that most hydrogels are nonsticky because of their high water content and hydrophilicity. Herein, a strategy to rapidly reverse the adhesion properties of hydrogels via surface anchoring very thin adhesive coatings is reported. Inspired by mussel adhesion, poly(vinyl alcohol) hydrogel is first coated with polymerized tannic acid that chelates with Fe 3+, which serves as the interface bonding layer. Subsequently, a wet adhesive poly(dopamine methacrylamide‐ co ‐methoxyethyl acrylate) is firmly anchored to form the very thin adhesive coating (<10 µm) that can generate high adhesion strength both in the air and underwater. The adhesive coating also endows hydrogels with high water retention capacity under warm condition (50 °C) and is able to get on‐demand functionalization on the designated area to achieve asymmetric adhesion, static and dynamic control over wettability. The strategy demonstrates potentials for broad applications from biomedicine to wearable electronics. Abstract : One kind of novel underwater adhesive hydrogels with robust underwater adhesion performance is engineered by anchoring mussel‐protein‐inspired copolymer onto poly(vinyl alcohol) hydrogel surface with tannic acid/Fe 3+ as bridge‐bonding layer. The adhesive hydrogels demonstrate good adhesion strengths both in dry and wet environments, cyclic adhesion performance, good water retention capacity, along with highly sensitive conductivity as artificial electronic skins.